The Role of Volunteers and Citizen Scientists in Addressing Declining Water Quality in Irish River Catchments. (6th May 2022) - Weiner, Donna; Bloomer, Julian; Conchúir, Ruairí Ó; Dalton, Catherine
Integrated Catchment Management (ICM) frames water management in Ireland to account for the complex hydrological, biophysical, and environmental interactions along with the political, socio-economic and cultural influences inherent in the management of river catchments. Despite a range of European Union (EU) Directives, national laws, policies, and incentives, the quality of water and biological diversity in Irish rivers is declining. In response, there has been an increased effort to involve local communities in ICM through a bottom-up, nature-based citizen science approach to activate local cooperation and environmental stewardship. This paper assembles 157 examples of citizen science water-based projects (48 in Ireland as of 2021) to appraise the position of community-led water monitoring in ICM. Notable differences found between the Irish and international programmes found a greater emphasis on habitat internationally, while a taxonomy focus was evident in Ireland despite a lower number of skilled volunteer activity-based citizen science projects. The continuing decline in water quality in Ireland, even with appropriate regulations, commendable governance changes, and expansion of citizen science, suggests more work is necessary before there will be successful ICM and improvements to river water quality.